Internationaler Kunstmarkt Köln 1979. - Beye, Peter (Köln : Messe- und Ausstellungs-Ges.m.b.H., 1979)
Duchamp, Marcel ; Ernst, Max ; Giacometti, Alberto ; Ray, Man ; Rothko, Mark ; Schlemmer, Oskar ; Schwitters, Kurt ; Tobey, Mark ; Wols ; etc.
Internationaler Kunstmarkt Köln 1979, 7. - 12.11.1979
Duits
boek